ANALISIS WILAYAH BERPOTENSI BANJIR DAERAH SUMATERA BARAT UNTUK PELAKSANAAN PEMBELAJARAN GEOGRAFI BERORIENTASI BENCANA ALAM - Muhammad Arif (STKIP Pesisir Selatan, 2019)
Flood disaster is one of the natural disasters that cause huge losses, especially in West Sumatra Province. For this reason, a disaster alert attitude is needed by the community and students as a form of disaster mitigation, one of which is through disaster-oriented learning activities through Geography. This study aims to identify areas in West Sumatra that are potentially affected by floods and identify the types of floods that often occur in the West Sumatra region in order to determine disaster mitigation efforts. The type of research conducted is qualitative descriptive. The method used is the study of literature from various references, both reading sources and data from the West Sumatra BNPB and BPBD. The type of data used is data obtained from documentation techniques, relevant sources, and disaster data from West Sumatra BPBD and BNPB. The results of this study show that the most potentially flooded areas are Padang Pariaman Regency, 50 Kota Regency, Agam Regency, Sijunjung Regency. Types of flooding that often occur are river flooding, flash floods, and urban drainage floods. It was concluded that the implementation of flood-oriented geography learning was most appropriate to be carried out in these 4 Regency.